2019
DOI: 10.1016/j.heliyon.2019.e02278
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of patients with primary HIV diagnosis in Kermanshah-Iran regarding the nature of HIV/AIDS: A qualitative study

Abstract: Background A diagnosis of HIV (human immunodeficiency virus) infection causes a wide range of mental challenges regarding the meaning and understanding of such a diagnosis because of the specific nature of HIV and its social consequences. AIDS patients perceived their disease as multidimensional Stigma and rejection and even discrimination and insult in receiving health services. Therefore, a deep awareness and understanding of an individual's meaning and interpretation of a HIV-positive diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Nurse clinicians should be sensitive to the unique set of emotional challenges that women diagnosed with HIV during pregnancy experience [ 26 ]. Of note is that the reactions observed are despite therapeutic advances in the ART that have redefined HIV as a chronic disease and echoed findings in other studies [ 23 , 40 , 41 ]. The women viewed HIV as a fatal illness despite all of them being asymptomatic at the time of receiving positive test results and had access to ART through PMTCT services.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Nurse clinicians should be sensitive to the unique set of emotional challenges that women diagnosed with HIV during pregnancy experience [ 26 ]. Of note is that the reactions observed are despite therapeutic advances in the ART that have redefined HIV as a chronic disease and echoed findings in other studies [ 23 , 40 , 41 ]. The women viewed HIV as a fatal illness despite all of them being asymptomatic at the time of receiving positive test results and had access to ART through PMTCT services.…”
Section: Discussionsupporting
confidence: 66%
“…The diagnosis of HIV was a traumatic and life-altering event, and they thought that death was imminent shortly after diagnosis. Barkish et al [ 41 ] argue that the progress made in the field of ART has not been successful in changing people’s perceptions about an HIV positive diagnosis. The perception and conceptualisation of HIV diagnosis as death, persist in many societies [ 17 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In his study, with a sample of 13 HIV-positive patients diagnosed at most six months before being interviewed, Fatemeh G.H. (2019) [ 32 ] and colleagues found that stigmatizing attitudes and discriminatory behaviors of other people, such as relatives and people in society, had a negative impact on the participants’ mental status, as well as on their perceptions and understanding about the medical diagnosis. Thus, the focus of care for people with HIV/AIDS should shift from therapeutic issues to socio-cultural ones.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study regarding the theme of stigma indicated three concepts of fear of being exposed, false judgment, and discrimination. The stigma of HIV infection is undoubtedly the most prominent problem in these patients, as it is related to the reactions of the different strata of society, in which the individual lives, and most importantly it is closely linked to emotional and psychological disorders (16).…”
Section: Discussionmentioning
confidence: 99%
“…While some studies are conducted on a social support network, stigma, quality of life, and familial problems among PLHIV in Iran (12)(13)(14)(15)(16)(17)(18)(19), more investigations are needed on different aspects of their living experience.…”
Section: Introductionmentioning
confidence: 99%